I'm trying to determine the convergence of this series: $$\sum \limits_{n=1}^\infty\left(\frac12·\frac34·\frac56·...\frac{2n-3}{2n-2}·\frac{2n-1}{2n}\right)^a$$ I've tried using D'Alambert criteria for solving it.

$$\lim_{n->\infty}\frac{(\frac12·\frac34·\frac56·...\frac{2n-3}{2n-2}·\frac{2n-1}{2n}\frac{2n}{2n+1})^a}{(\frac12·\frac34·\frac56·...\frac{2n-3}{2n-2}·\frac{2n-1}{2n})^a} = \lim_{n->\infty}\left(\frac{(\frac12·\frac34·\frac56·...\frac{2n-3}{2n-2}·\frac{2n-1}{2n}·\frac{2n}{2n+1})}{(\frac12·\frac34·\frac56·...\frac{2n-3}{2n-2}·\frac{2n-1}{2n})}\right)^a$$ Which becomes: $$\lim_{n->\infty}\left(\frac{2n}{2n+1}\right)^a$$ But after that, the limit is 1, so its convergence is unknown. Any idea?


Let $$a_n={1\over2}\cdot{3\over4}\cdot{5\over6}\cdot\ \cdots\ \cdot {{2n-3}\over{2n-2}}\cdot{{2n-1}\over{2n}}.$$

Note that $a_{n+1}=a_n\cdot {2n +1\over2(n+1)}$.

We will show that for all $n$: $$ {1\over\sqrt{ 4n}} \le a_n\le {1\over\sqrt{ 2n+1}}. $$ Having established this, it will follow by comparison with $p$-series that $\sum\limits_{n=1}^\infty a_n^a$ converges if and only if $a>2$.

We establish the inequalities by induction.

Towards showing that $ a_n\le {1\over\sqrt{ 2n+1}}$, first note that $a_1\le {1\over \sqrt{2\cdot 1+1}}$.

Now suppose $a_n \le {1\over\sqrt{ 2n+1}}$. Then $$ a_{n+1}^2\le \biggl[\,{2n +1\over 2(n+1)}\biggr]^2\cdot{1\over 2n+1} ={2n+1\over 4(n+1)^2}={2n+1\over 4n^2+8n+4}\le{2n+1\over 4n^2+8n+1 }={1\over 2n+1}.$$

So, $a_n\le {1\over\sqrt {2n+1}}$ for all $n$.

Towards showing that $ {1\over\sqrt{ 4n}} \le a_n$, first note that $a_1\ge {1\over \sqrt{4\cdot 1 }}$.

Now suppose $a_n \ge {1\over\sqrt{ 4n}}$. Then $a_{n+1}^2\ge \Bigl[\,{2n +1\over 2(n+1)}\,\Bigr]^2\cdot{1\over 4n}$. Now $$ \biggl[\,{2n +1\over 2(n+1)}\,\biggr]^2\cdot{1\over 4n}-{1\over 4(n+1)} ={1\over 16 n(n+1)^2}>0;$$ thus $$ a_{n+1}^2\ge{1\over 4(n+1)}. $$

So, $a_n\ge {1\over\sqrt {4n}}$ for all $n$.


Rewrite the summand in terms of factorials like this: $$ \left( \frac{(2n)!}{ 2^{2n} (n!)^2} \right)^a .$$ Applying Stirling's approximation gives $$ \frac{(2n)!}{ 2^{2n} (n!)^2} \sim \frac{1}{\sqrt{\pi n} } $$ so to finish off, apply what you know about the convergence of $ \displaystyle \sum \frac{1}{n^p} $ for various $p.$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.